One-Dimensional ZnO Nanorod Array Grown on Ag Nanowire Mesh/ZnO Composite Seed Layer for H2 Gas Sensing and UV Detection Applications - Fang-Hsing Wang; An-Jhe Li; Han-Wen Liu; Tsung-Kuei Kang (Sensors, 2024)
Photodetectors and gas sensors are vital in modern technology, spanning from environmental monitoring to biomedical diagnostics. This paper explores the UV detection and gas sensing properties of a zinc oxide (ZnO) nanorod array (ZNA) grown on silver nanowire mesh (AgNM) using a hydrothermal method. We examined the impact of different zinc acetate precursor concentrations on their properties. Results show the AgNM forms a network with high transparency (79%) and low sheet resistance (7.23 Ω/□). A sol–gel ZnO thin film was coated on this mesh, providing a seed layer with a hexagonal wurtzite structure. Increasing the precursor concentration alters the diameter, length, and area density of ZNAs, affecting their performance. The ZNA-AgNM-based photodetector shows enhanced dark current and photocurrent with increasing precursor concentration, achieving a maximum photoresponsivity of 114 A/W at 374 nm and a detectivity of 6.37 × 1014 Jones at 0.05 M zinc acetate. For gas sensing, the resistance of ZNA-AgNM-based sensors decreases with temperature, with the best hydrogen response (2.71) at 300 °C and 0.04 M precursor concentration. These findings highlight the potential of ZNA-AgNM for high-performance UV photodetectors and hydrogen gas sensors, offering an alternative way for the development of future sensing devices with enhanced performance and functionality.